PENGARUH MULTIMEDIA, GAYA BELAJAR DAN MOTIVASI BELAJAR TERHADAP PENINGKATAN PRESTASI BELAJAR MIKRO EKONOMI MAHASISWA PENDIDIKAN EKONOMI FKIP UNLAM 2012/2013 - Baseran Nor; Baedhowi Baedhowi; Djoko Santoso Th (Jurnal Pendidikan Insan Mandiri, 2013)
Learning technologies is necessary in the learning process, because it can spread the information widely, evenly, fast, uniform and integrated so that the message can be delivered in accordance with the content in question. Technology can be a medium for faculty in order to realize the learning process that is effective, efficient, and productive in accordance with the needs and demands of students. This study aimed to determine differences in learning achievement Micro Economics course student of Economics Faculty of Teacher Education UNLAM seen from the use of multimedia, learning styles and learning motivation of students.The research method used was a 2x3x2 factorial quasi-experimental. This research makes the entire population as the entire population of students taking courses in Micro Economics odd semester 2012/2013 as respondents, amounting to 72 students. Data collection using tests, questionnaires and documentation. Data were analyzed using three-way ANOVA analysis.Conclusions derived from this research are: 1) there are differences in learning achievement of students who use the Micro Economic multimedia with conventional media, 2) there are differences in student achievement visual, auditory and kinesthetic, 3) there are differences in student achievement Micro Economics Economics Education courses FKIP UNLAM that have high and low motivation, 4) there is an interaction effect between the use of multimedia to the type of student learning styles, 5) there is no interaction effect between the use of multimedia on the level of student motivation, 6) there is an interaction effect between type of learning style with the level of student motivation, and 7) there is no effect of the interaction effect of the use of multimedia, learning style type, and level of student motivation to learn.